Pengembangan Model Manajemen Kinerja Strategis pada Koperasi Pegawai Republik Indonesia: Bagian 2 - Murwani, F. Danardana; ., H. Suharto S.M (Universitas Brawijaya, Indonesia, 2012)
The second-phase developmental research was intended to produce a model, namely the KPRI’sstrategic performance management (SPM) model. The effectiveness of model was verified through fieldtesting based on pre-test/post-test without control group design in workshop forum. The sample was takenby using a purposive technique including sample of KPRIs and personnel samples of KPRI. Data wereanalyzed by using paired-samples t test and one-sample t test. The result showed that the field testing ofmodel in workshop forum: (1) contributed positively to KPRIs personnels attitude; (2) affected in increasingKPRIs personnels knowledge of the model principles; and (3) was effective in both its process andproduct. Following up the field testing of model in workshop forum, the further researches based on operationalfield testing are very important to conduct. In operational field testing, the effectiveness of model willbe verified through daily activities of KPRI.